Agricultural business and life sciences in European agricultural law - Albisinni, Ferdinando (Przegląd Prawa Rolnego, 2021)
The article focuses on the evolutionary trends of agricultural law in a European perspective, highlighting the challenges and problematic issues that have accompanied the choices made in the context of the Common Agricultural Policy in the 21st century. In this perspective, particular attention has been paid to the issues of the agricultural business and the subject of the limits of agricultural activity; these are issues raised in the Italian legal system, but also relevant to the Polish legal system, as Roman Budzinowski has repeatedly stressed in his works. The analysis considers in particular the reforms of the present century, from the Mid-Term Review 2003 to the reforms of 2013 and of 2021, when there occurred a rediscovery of agriculture as a productive activity; it also highlights the emergence of new systemic models that eventually formed the European agricultural codes. Then, the most recent innovations introduced by the Lisbon Treaty are recalled, starting from some recent regulations on official controls and Commission documents on the European Green Deal and animal welfare, to the protection of all forms of life and the environment in its complexity and unity, which leads to the conclusion that the complex events of the first two decades of the 21st century are marked by an increasing attention directed towards the life sciences seen as an essential and distinctive element of the activity of an agricultural enterprise in all its forms.